Contemporary Themes in Education Policy - Zhou, Xin (Journal of Education and Educational Technologies, 2023)
Since the conclusion of the Belfast Agreement in 1998, whilst Northern Ireland is part of the UK, it has had the right to set its education policy independently of its county of origin (O'Connor et al., 2020). As a result, Northern Ireland has a separate Statutory Curriculum for Key Stage 3: Principles and Details. The aim of this paper is to critically analyse the educational ideology embodied in KS3 and the globalisation trends of the period corresponding to the policy context. The policy is systematically analysed using theoretical concepts such as Human capital and Social Efficiency to shed further light on the historical and economic context in which KS3 has emerged.